2016
DOI: 10.20853/26-4-197
|View full text |Cite
|
Sign up to set email alerts
|

Exploring students motives for studying psychology: a qualitative study

Abstract: The present study explored participants' motives for studying psychology. A qualitative, exploratory, descriptive and contextual research design was used. The research method consisted of a brief survey. Four Black participants (male = 2; female = 2) for the study were purposefully selected from a Historically Black institution of higher learning in South Africa. The data collected through audio-taped individual, semi-structured interviews were analyzed by means of content analysis. The participants were asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Further, it should not be assumed that students assume the responsibility of selfcare with the insight or skills required to implement healthy self-care practices or that they use available resources for self-care. Previous studies have reported that university students adopt ineffective self-care and coping strategies, and struggle to access support services that could help them in managing challenges (Mudhovozi, 2011;Naidoo et al, 2014). Consistent with the literature, our study found that none of the students mentioned using available student counselling support services within the university to enhance their self-care.…”
Section: Psychological Self-caresupporting
confidence: 84%
See 1 more Smart Citation
“…Further, it should not be assumed that students assume the responsibility of selfcare with the insight or skills required to implement healthy self-care practices or that they use available resources for self-care. Previous studies have reported that university students adopt ineffective self-care and coping strategies, and struggle to access support services that could help them in managing challenges (Mudhovozi, 2011;Naidoo et al, 2014). Consistent with the literature, our study found that none of the students mentioned using available student counselling support services within the university to enhance their self-care.…”
Section: Psychological Self-caresupporting
confidence: 84%
“…Therefore, navigating the intersection of major life transitions with the COVID-19 pandemic may have been challenging for first-year students. Research examining firstyear experiences suggests that the challenges related to transitioning into university often prevent students from being able to care for themselves adequately (Ayala et al, 2018;Mudhovozi, 2011;Naidoo et al, 2014). For example, Bantjes et al (2022) found higher rates of non-fatal suicidal behaviour among first-year university students in South Africa.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Moreover, students must access proper study resources to cope with and potentially optimise study demands. Mudhovozi (2011) affirms that students are inclined to view demands as a positive challenge rather than a hindrance when they perceive their study resources as adequate. Study resources can help students deal with demands and include support from lecturers, family, friends and developmental opportunities (Cilliers et al, 2018).…”
Section: The Relationship Of Proactive Behaviour Towards Strengths Us...mentioning
confidence: 88%
“…Indeed, research has found that specific job demands or job stressors, such as time constraints, can promote proactive behaviour (Bakker & Demerouti, 2017Parker et al, 2019). It can also be argued that students can experience specific demands as challenging rather than hindering, in this case, when they can use their strengths to overcome these challenges (Mudhovozi, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Women who plan to start a family in the future show significant differences in terms of the motives underlying their college/university application decisions. The subject literature mentions the so-called 'caregiving roles and responsibilities', which are the main factors determining young women's field-of-study decisions (Mudhovozi, Maree, 2012). One common motive fundamental in the pursuit of higher education is primarily the desire to develop one's own interests and deepen one's knowledge (Jarecki, The unique corporate knowledge involved in the processes of effective development as well as production and marketing of appropriately defined products and services, concerning the organization and management of these processes in particular.…”
Section: Literature Review 21 Sustainable Educationmentioning
confidence: 99%